SMALL STRUCTURES IN RIVERS AND THEIR EFFECTS ON LANDSCAPE CONNECTIVITY - LOWER COURSE OF THE PIANCÓ RIVER - BRAZILIAN SEMI-ARID REGION - Castelo Branco, André Oliveira Trigueiro; Souza, Jonas Otaviano Praça de (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
This study investigates landscape connectivity in semi-arid fluvial systems, focusing on the effects of anthropogenic structures on water and sediment transmission. The research was conducted in the lower course of the Piancó River basin, where twenty-four anthropogenic structures were identified and characterized, including fords and dams (both rudimentary and engineered). The disordered distribution of these structures highlights the lack of planning in human interventions. The analysis demonstrated that engineered dams, in particular, disconnect the eastern portion of the basin from the effective catchment area (ECA), affecting hydrological and sediment dynamics. It is concluded that anthropogenic structures exert significant local influence on fluvial channels, necessitating continuous monitoring and an integrated approach with other research to better understand the impacts. It is recommended that preliminary connectivity mapping be incorporated in the initial stages of fluvial geomorphology research to improve the precision and effectiveness of analyses.